Serial sabotage (Nancy Drew: girl detective, 43, 1, 2010)
When a cash box is stolen from a visiting carnival, Nancy endeavors to clear the name of her accused friend, Ned, and uncovers a complicated plot involving financial mismanagement, a setup and other sinister activities.